Synthesis and biological activities of diflunisal hydrazide-hydrazones - KÜÇÜKGÜZEL, ŞÜKRİYE GÜNİZ (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2003)
Several diflunisal hydrazide-hydrazone derivatives namely 2',4'-difluoro-4-hydroxybiphenyl-3-carboxylic acid [(5-nitro-2-furyl/substitutedphenyl)methylene] hydrazide (3a-o) have been synthesised. Methyl 2',4'-difluoro-4-hydroxybiphenyl-3-carboxylate (1) and 2',4'-difluoro-4-hydroxybiphenyl-3-carboxylic acid hydrazide (2) were also synthesised and used as intermediate compounds. All synthesised compounds were screened for their antimycobacterial activity against Mycobacterium tuberculosis H37 Rv, antimicrobial activities against various bacteria, fungi and yeast species. Compound 3a have shown activity against Staphylococcus epidermis HE-5 and Staphylococcus aureus HE-9 at 18.75 and 37.5 mug mL(-1), respectively. Compound 3o have exhibited activity against Acinetobacter calcoaceticus IO-16 at a concentration of 37.5 mug mL(-1), whereas Cefepime, the drug used as standard, have been found less active against the microorganisms mentioned above. The synthesised compounds were found to provide 12-34% inhibition of mycobacterial growth of M. tuberculosis H37 Rv in the primary screen at 6.25 mug mL-1. Anticonvulsant activity of the compounds were also determined by maximal electroshock (MES) and subcutaneous metrazole (scMET) tests in mice and rats following the procedures of antiepileptic drug development (ADD) program of the National Institutes of Health (NIH). Compound 3k showed 25% protection against MES induced seizures in p.o. rat screening at a dose level of 30 mg kg(-1) whereas 3n and 3o showed neurotoxicity after 4 and 0.5 h at a dose level of 100 and 300 mg kg(-1) respectively. (C) 2003 Editions scientifiques et medicales Elsevier SAS. All rights reserved.
Keywords: hydrazide-hydrazones; diflunisal; antibacterial activity; anticonvulsant activity; HETCOR; ANTITUBERCULOTIC ACTIVITY; ANTICONVULSANT ACTIVITY; DERIVATIVES; ACID; 4-THIAZOLIDINONES; SEMICARBAZONES; PRODUCTS; AGENTS